Acquisition and Disclosure of Information as a Hold-up Problem - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
The acquisition of information prior to sale gives rise to a hold-up situation quite naturally. Yet, while the bulk of the literature on the hold-up problem considers negotiations under symmetric information where cooperative short-cuts such as split the difference capture the outcome of bargaining, in the present setting, parties negotiate under asymmetric information where the outcome must be derived from a non-cooperative bargaining procedure. To avoid the difficult task of specifying and solving complicated games combining elements of signalling and screening, but to still compare incentives for acquiring information under voluntary versus mandatory disclosure, use of conditions such as incentive, disclosure and participation constraints only is made that are common to all non-cooperative bargaining outcomes.
urn:nbn:de:bvb:19-epub-17333-0
Keywords: K12; K13; 330; mistake; information acquisition; disclosing information